Efficiency of standardized ileal digestible lysine utilization for whole body protein deposition in pregnant gilts and sows during early-, mid-, and late-gestation. (21st October 2020) - Ramirez-Camba, Christian D; Dunn, James L; Htoo, John K; González-Vega, Jolie C; Touchette, Kevin; Samuel, Ryan S; Levesque, Crystal L
Abstract: The efficiency of SID Lys utilization (kSID Lys) in gilts and sows during early (days 48 to 52), mid (days 75 to 79), and late gestation (days 103 to 107) was investigated using 88 pregnant females (PIC 1050; 27 gilts, 27 parity 1 sows, 34 parity 2+ sows; 192.96 ± 22.84 kg at days 42 ±1 of gestation) and whole body nitrogen (N) retention balance studies. Females were assigned to 1 of 4 SID Lys levels ranging from 40% to 70% of the daily SID Lys requirements above maintenance for a parity 1 sow according to the NRC (2012) gestating sow model in each gestation period. Experimental diets were isocaloric (3, 335 kcal ME/kg) and isoproteic (11.75 % CP) and dietary indispensable AA were set to meet or exceed 100% of AA:Lys ratios. The slope of the linear response to graded SID Lys intake was defined as kSID Lys. With the aim of increasing the accuracy of kSID Lys estimates, gilt data from the current study was combined with gilt data from a previous study conducted at the same facility using 4 SID Lys levels ranging from 60% to 90% of the daily SID Lys requirements above maintenance for gilts according to the NRC (2012) gestating sow model. Whole body Lys retention of the combined gilt data set was assessed with different broken-line and nonlinear models. The kSID Lys was 0.65, 0.38, and 0.52 for early-, mid-, and late-gestation, respectively, in gilts. A linear response to graded SID Lys intake was found in late gestation only in parity 1 and 2+ sows; kSID Lys was determined as 0.44 and 0.52 in late gestation for parity 1 and parity 2+ sows, respectively. There were no differences in kSID Lys in late gestation between parities. For the combined gilt data, the model of best performance (reduced error and greater goodness of fit) was the Hoerl model. Maximum kSID Lys (i.e., g SID Lys retention/g SID Lys intake) in gilts was 0.67, 0.54, and 0.53 in early, mid, and late gestation predicted at 7.2, 9.1, and 13.5 g of SID Lys intake/d, respectively, based on the Hoerl model. Maximum SID Lys retention in gilts was similarly predicted at 8.5, 10.5, and 20.9 g of SID Lys intake per day in early, mid, and late gestation and resultant kSID Lys of 0.61, 0.51, and 0.44, respectively. The findings of this study demonstrate that kSID Lys varies by stage of gestation and SID Lys intake level and that, at least in gilts, a dynamic kSID adjusted for daily intake more adequately reflects biological response and hence allows more precise feeding of pregnant females.